EFFECTIVENESS OF DIFFERENTIATED LEARNING STRATEGIES IN IMPROVING THE WRITING SKILLS POETRY OF STUDENTS IN ELEMENTARY SCHOOL - Indri Pudjiati; Nidya Chandra Muji Utami; Fahrurrozi (Jurnal Cakrawala Pendas, 2023)
Indonesian language learning in poetry writing skills for students needs to be explored properly and correctly because this skill does not come by itself, regular and programmed practice is needed, so that the writing process becomes more directed and students are able to find ideas or ideas for writing poetry. One of the learning strategies that can be used in writing poetry for elementary school students is a differentiated learning strategy. This study aims to determine the effectiveness of differentiated learning strategies in improving students' poetry writing skills in elementary schools. The method used in this research is quasi-experiment, with a one-group pretest-posttest design or before-after design. The data collection technique used was formative assessment for the learning process (assessment for learning) in the form of observation notes. The observation instrument used was a rubric for the performance of poetry writing skills. The population in this study were students of grades VA and VB of SDN Sangkali, Citeureup District, Bogor Regency. The research sample used a random purpose technique which amounted to 30 students consisting of 15 male students and 15 female students. The results of this study can be concluded that there is the effectiveness of differentiated learning strategies in improving students' poetry writing skills in elementary schools. The implication of this research is that it can be used as reference and evaluation material in the application of differentiated learning strategies in other language skills besides writing such as reading, speaking, and listening in the future. Pembelajaran Bahasa Indonesia pada keterampilan menulis puisi bagi siswa perlu digali dengan baik dan benar, karena keterampilan ini tidak datang dengan sendirinya, diperlukan latihan yang teratur dan terprogram, sehingga proses kepenulisan menjadi lebih terarah dan siswa mampu menemukan ide atau gagasan menulis puisinya. Salah satu strategi pembelajaran yang dapat digunakan dalam menulis puisi bagi siswa sekolah dasar adalah strategi pembelajaran berdiferensiasi. Penelitian ini bertujuan untuk mengetahui efektivitas strategi pembelajaran berdiferensiasi dalam meningkatkan keterampilan menulis puisi siswa di sekolah dasar. Metode yang digunakan dalam penelitian ini adalah kuasi eksperimen, dengan desain one-group pretest-posttest design atau before-after design. Teknik pengumpulan data yang digunakan yakni asesmen formatif untuk proses pembelajaran (assessment for learning) berupa catatan observasi. Instrumen observasi yang digunakan yaitu rubrik unjuk kerja keterampilan menulis puisi. Populasi dalam penelitian ini merupakan siswa kelas VA dan VB SDN Sangkali Kecamatan Citeureup Kabupaten Bogor. Sampel penelitian menggunakan teknik acak bertujuan yaitu berjumlah 30 orang siswa terdiri dari 15 siswa laki-laki dan 15 siswa perempuan. Hasil penelitian ini dapat disimpulkan terdapat keefektifan strategi pembelajaran berdiferensiasi dalam meningkatkan keterampilan menulis puisi siswa di sekolah dasar. Implikasi dalam penelitian ini yaitu bisa dijadikan bahan referensi dan evaluasi dalam penerapan strategi pembelajaran berdiferensiasi pada keterampilan berbahasa lain selain menulis seperti membaca, berbicara dan menyimak kedepannya.